The endophytic fungus Cosmosporella sp. VM-42 from Vinca minor is a source of bioactive compounds with potent activity against drug-resistant bacteria - Ting He; Xiao Li; Rosario del Carmen Flores-Vallejo; Ana-Maria Radu; Jan Maarten van Dijl; Kristina Haslinger (Current Research in Microbial Sciences)
Medicinal plants serve as valuable resources for the isolation of endophytic fungi. Vinca minor is a well-known producer of important vinca alkaloids and emerges as a promising source of endophytic fungi with antibacterial potential and biosynthetic capacity. In this study, we isolated an endophytic fungus from V. minor and identified it as Cosmosporella sp. VM-42. To date, relatively little is known about this fungal genus. The ethyl acetate extract of this isolate selectively inhibited Gram-positive bacteria, such as methicillin-sensitive and methicillin-resistant Staphylococcus aureus (MSSA and MRSA). Therefore, we isolated the most abundant compound from the crude extract and identified it as nectriapyrone with MIC and MBC values ranging from 125 to 62.5 µg/mL against MSSA and MRSA strains. We further sequenced and annotated the 39.07 Mb genome of the isolate, revealing that it encodes 9842 protein-coding genes, including 415 genes for carbohydrate-active enzymes and various biosynthetic gene clusters. Our untargeted metabolomic analysis shows that the fungus produces various secondary metabolites, including cyclodepsipeptides, dimeric naphtho-γ-pyrones, and macrolactones, which are known to have antifungal and antibacterial activities. In addition, we used small-molecule epigenetic modulators to activate the expression of silent biosynthetic gene clusters to broaden the chemical profile of Cosmosporella sp. VM-42. Taken together, we provide a first systematic analysis of Cosmosporella sp. VM-42, and our results show that it is a promising source of compounds with pharmacological potential against drug resistant bacteria.